Ionotropic P2X ATP Receptor Channels Mediate Purinergic Signaling in Mouse Odontoblasts - Shiozaki, Yuta; Sato, Masaki; Kimura, Maki; Sato, Toru; Tazaki, Masakazu; Shibukawa, Yoshiyuki (Frontiers in Physiology, 2017)
ATP modulates various functions in the dental pulp cells, such as intercellular communication and neurotransmission between odontoblasts and neurons, proliferation of dental pulp cells, and odontoblast differentiation. However, functional expression patterns and their biophysical properties of ionotropic ATP (P2X) receptors (P2X1-P2X7) in odontoblasts were still unclear. We examined these properties of P2X receptors in mouse odontoblasts by patch-clamp recordings. K+-ATP, nonselective P2X receptor agonist, induced inward currents in odontoblasts in a concentration-dependent manner. K+-ATP-induced currents were inhibited by P2X4 and P2X7 selective inhibitors (5-BDBD and KN62, respectively), while P2X1 and P2X3 inhibitors had no effects. P2X7 selective agonist (BzATP) induced inward currents dose-dependently. We could not observe P2X1,2/3,3 selective agonist (αβ-MeATP) induced currents. Amplitudes of K+-ATP-induced current were increased in solution without extracellular Ca2+, but decreased in Na+-free extracellular solution. In the absence of both of extracellular Na+ and Ca2+, K+-ATP-induced currents were completely abolished. K+-ATP-induced Na+ currents were inhibited by P2X7 inhibitor, while the Ca2+ currents were sensitive to P2X4 inhibitor. These results indicated that odontoblasts functionally expressed P2X4 and P2X7 receptors, which might play an important role in detecting extracellular ATP following local dental pulp injury.